Albania : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
This report presents an Ex Post Assessment of Albania's Longer-Term-Program Engagement with the IMF. Albania has been engaged in a series of IMF-supported programs since the beginning of transition. This report provides an overview of economic developments and the overall role of the IMF in Albania. It reviews the implementation of financial policies, and looks into selected dimensions of structural policies. The report summarizes the record on meeting conditionality and the nature of Bank-IMF collaboration. The considerations for future program engagement are also examined.